Pengetahuan Ibu Mengenai Gizi Seimbang pada Pengukuran Antropometri (TB/U) Balita - Purnama, Anita; Eriyani, Theresia; Mulya, Adelse Prima; Rahayuwati, Laili; Mirwanti, Ristina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study analyzes the relationship between maternal knowledge regarding balanced nutrition and anthropometric measurements (TB/U) in toddlers in Sukamulya Village. The method used is quantitative correlational. The study results showed that maternal knowledge regarding balanced nutrition and the incidence of stunting obtained a p-value of 0.889. In conclusion, there is no significant relationship between maternal knowledge about balanced nutrition and the incidence of stunting in Hamlet 3, Sukamulya Village, Bandung Regency. Keywords: Anthropometrics, Balanced Nutrition, Knowledge, Stunting